2022
DOI: 10.3390/nano12071079
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Platinum Nanoparticles (PtNPs) Synthesis by Acid Phosphatase Mediated Eco-Benign Combined with Photocatalytic and Bioactivity Assessments

Abstract: Noble metal nanoparticles (NMNPs) are viable alternative green sources compared to the chemical available methods in several approach like Food, medical, biotechnology, and textile industries. The biological synthesis of platinum nanoparticles (PtNPs), as a strong photocatalytic agent, has proved as more effective and safer method. In this study, PtNPs were synthesized at four different temperatures (25 °C, 50 °C, 70 °C, and 100 °C). PtNPs synthesized at 100 °C were smaller and exhibited spherical morphology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…Figure d indicates a single peak at 399.8 eV that is attributed to N 1s core levels. Figure e exhibits the high-resolution spectra of Pt 4f where binding energies of Pt 4f 5/2 and 4f 7/2 were located at 75.1 and 72.5 eV, respectively, close to those reported in the literature, implying that rather than Pt 2+ , the PtNPs inside the hydrogel were in the metallic Pt 0 form. It is worth noting that we hereby refer to PtNPs in an environment where carboxylates and amines might loosely bind to the surface of PtNPs and this can contribute to the binding events.…”
Section: Resultssupporting
confidence: 81%
“…Figure d indicates a single peak at 399.8 eV that is attributed to N 1s core levels. Figure e exhibits the high-resolution spectra of Pt 4f where binding energies of Pt 4f 5/2 and 4f 7/2 were located at 75.1 and 72.5 eV, respectively, close to those reported in the literature, implying that rather than Pt 2+ , the PtNPs inside the hydrogel were in the metallic Pt 0 form. It is worth noting that we hereby refer to PtNPs in an environment where carboxylates and amines might loosely bind to the surface of PtNPs and this can contribute to the binding events.…”
Section: Resultssupporting
confidence: 81%
“…Uncooked samples were placed randomly in coded covered cups. Fifteen semi-trained panelists were asked to evaluate the refrigerated stored meatballs for rancid odor three times repeatedly for 15 s with an interval of 30 s in the analysis on days 0, 3, 6, 9, and 12. en, the color attributes were evaluated using the same manner [26].…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Morsy et al [15] stated that the nano-pomegranate peel had remarkable effect to retard the lipid and protein oxidation and consequently prolong the shelf life of meatballs. Jouki and Khazaei [26] reported that oxidative rancidity (TBARS) and sensory quality of cold stored (4 °C) camel meat can be easily enhanced by controlling the packaging atmosphere.…”
Section: Sensory Propertiesmentioning
confidence: 99%
“…In addition, recent emerging and chemical-free technologies related to in situ detection of the physicochemical changes in the biological media are important for studying the cellular-based levels and the functional components concentrations, such as Raman, circular dichroism (CD), and nuclear magnetic resonance (NMR) [ 73 , 74 ]. Several studies have documented the efficacy of these technologies for the replacement, enhancement, and improvement of various conventional analytical techniques in detecting animal and plant tissues [ 75 , 76 , 77 , 78 , 79 , 80 ]. On the other hand, these methods have common linked challenges, such as the fluorescence dye intervention on the used photonic optical sensors.…”
Section: Application Of Acoustic Sensors In Biochemical Materials Det...mentioning
confidence: 99%